2016
DOI: 10.3390/molecules21070930
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Determination of Alkaloids in Lotus Flower (Flower Buds of Nelumbo nucifera) and Their Melanogenesis Inhibitory Activity

Abstract: A quantitative analytical method for five aporphine alkaloids, nuciferine (1), nornuciferine (2), N-methylasimilobine (3), asimilobine (4), and pronuciferine (5), and five benzylisoquinoline alkaloids, armepavine (6), norarmepavine (7), N-methylcoclaurine (8), coclaurine (9), and norjuziphine (10), identified as the constituents responsible for the melanogenesis inhibitory activity of the extracts of lotus flowers (the flower buds of Nelumbo nucifera), has been developed using liquid chromatography-mass spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 29 publications
2
42
0
Order By: Relevance
“…Pronuciferine Anti-obesity, Anti-oxidant (Ma et al, 2015), Anti-melanogenesis (Morikawa et al, 2016) models, and the results were similar to that of standard antipyretic drug, paracetamol (Sinha et al, 2000). Immune-modulatory activity of N. nucifera rhizome was evaluated, and the study found that treatment of rhizome inhibited mast cell degranulation and LPS induced activation of macrophages (Mukherjee et al, 2010).…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Pronuciferine Anti-obesity, Anti-oxidant (Ma et al, 2015), Anti-melanogenesis (Morikawa et al, 2016) models, and the results were similar to that of standard antipyretic drug, paracetamol (Sinha et al, 2000). Immune-modulatory activity of N. nucifera rhizome was evaluated, and the study found that treatment of rhizome inhibited mast cell degranulation and LPS induced activation of macrophages (Mukherjee et al, 2010).…”
mentioning
confidence: 55%
“…Anti-pyretic potential of ethanolic extract from N. nucifera stalks was evaluated on normal body temperature and yeast induced pyrexia in rats. It was found that the extract caused significant lowering of body temperature in both Nuciferine Hepato-protective (Ma et al, 2015, Anti-cancer (Liu et al, 2015, Anti-inflammatory , Insulin secretagogue (Nguyen et al, 2012), (Hu et al, 2010), Antipsychotic (Farrell et al, 2016), Anti-melanogenesis (Morikawa et al, 2016), hERG blocker (Grienke et al, 2015) 3…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of isoquinoline alkaloids in the extracts from flower buds of Nelumbo nucifera Gaertn. was performed by addition of acetic acid [14].…”
Section: Chromatographic Separation Methodsmentioning
confidence: 99%
“…Peanut shells are products of peanut crop and ones generally disposed of as waste, but it actually contains high antioxidants potential with total polyphenols, flavonoids, contents of amino acids, alkaloids, and terpenes [5,6]. Some previous studies have proven the ability of flavonoids and alkaloids as anti-tyrosinase [7,8]. In this study, we used a variety of solvents to attract various active compounds contained in peanut shells to assess the anti-tyrosinase activity.…”
Section: Introductionmentioning
confidence: 99%